2020
DOI: 10.1242/dev.179168
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans Flamingo FMI-1 controls dendrite self-avoidance through F-actin assembly

Abstract: Self-avoidance is a conserved mechanism that prevents crossover between sister dendrites from the same neuron, ensuring proper functioning of the neuronal circuits. Several adhesion molecules are known to be important for dendrite self-avoidance, but the underlying molecular mechanisms are incompletely defined. Here, we show that FMI-1/Flamingo, an atypical cadherin, is required autonomously for self-avoidance in the multidendritic PVD neuron of Caenorhabditis elegans. The fmi-1 mutant shows increased crossove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…This result is in agreement with earlier works that have shown that 3-way junctions represent the minimal energy shape for connecting tubular membrane surfaces [64]. Yet, the observed junction geometry may also be influenced by a local effect of cytoskeletal proteins or membrane coating proteins [65][66][67][68][69][70]. Our findings can therefore serve as a basis for further study of the physical mechanism for stabilization of PVD junctions.…”
Section: Three-way Symmetry Of Pvd Junctions Generates Orthogonal Treessupporting
confidence: 92%
“…This result is in agreement with earlier works that have shown that 3-way junctions represent the minimal energy shape for connecting tubular membrane surfaces [64]. Yet, the observed junction geometry may also be influenced by a local effect of cytoskeletal proteins or membrane coating proteins [65][66][67][68][69][70]. Our findings can therefore serve as a basis for further study of the physical mechanism for stabilization of PVD junctions.…”
Section: Three-way Symmetry Of Pvd Junctions Generates Orthogonal Treessupporting
confidence: 92%
“…Flamingo is supposed to communicate polarity between neighboring cells and direct the formation of polarized structures via homophilic interactions in many contexts [37]. Molecule-mediated cell-tocell interactions are critical for cellular behaviors involved in many biological processes, such as neuronal migration, self-avoidance of neurite outgrowth, ommatidial formation and epithelial cell organization, and the abnormalities were widely reported in flamingo mutation [38][39][40][41][42]. Celsr2 knockout mice were partially reminiscent of these phenotypes during development, including defective migration of facial motoneurons [26], abnormal cilial organization [27].…”
Section: Discussionmentioning
confidence: 99%
“…2018 ). Similarly, mutations in the atypical cadherin FMI-1 /Flamingo result in self-avoidance defects, likely through misregulation of the actin cytoskeleton ( Hsu et al . 2020 ).…”
Section: Guided Assembly Of Pvd Dendritesmentioning
confidence: 99%